2010
DOI: 10.1007/s10340-010-0313-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of geochemical composition of diatomaceous earth on its insecticidal activity against adults of Sitophilus oryzae (L.) (Coleoptera: Curculionidae)

Abstract: Laboratory experiments were done to determine the effect of geochemical composition of diatomaceous earth (DE) on insecticidal activity of DE against adults of the rice weevil, Sitophilus oryzae (L.) (Coleoptera: Curculionidae). Samples of DE were mined from DE-deposits in Slovenia, Greece, and Serbia. In addition, a commercially available DE formulation (SilicoSec Ò ) was used in the tests and served as a positive control. The bioassays were carried out at temperatures 20, 25, and 30°C, relative humidity leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…In recent times, the use of environmentally acceptable substances for pest control in agriculture has gained unprecedented impetus all over the world (Radwan & El-Zemity, 2007;Rojht et al, 2010;Singh et al, 2010). Different natural substances are promoted due to their wide range of ideal properties, such as high results have shown that the largest share of mass was lost by those slugs which were treated with hydrated lime individually or in combination with other substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, the use of environmentally acceptable substances for pest control in agriculture has gained unprecedented impetus all over the world (Radwan & El-Zemity, 2007;Rojht et al, 2010;Singh et al, 2010). Different natural substances are promoted due to their wide range of ideal properties, such as high results have shown that the largest share of mass was lost by those slugs which were treated with hydrated lime individually or in combination with other substances.…”
Section: Discussionmentioning
confidence: 99%
“…; Zagorje ob Savi, Slovenia), diatomaceous earth (from Bela Cerkva at Dolenjska region, Slovenia) (Rojht et al, 2010), and sawdust (from beechwood, finely ground). The said substances were studied individually or in combination in the ratio 1:1 (the studied substances were of the same weight and mixed in larger vessels).…”
Section: Experimental Designmentioning
confidence: 99%
“…Handling of the temperature of the grains and the post-inert employment, such as diatomaceous earth, are examples of non-chemical promising methods for the integrated handling of insect pests of stored products Wakil et al, 2010). Diatomaceous earth is originated from sediment of carapaces of diatomaceous algae and when in contact with insects cause the removal of the layer of wax from their cuticle, bringing about their death by dissection (Rojht et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This product acts on larvae and adult insects, adhering to their body as they move on the surface or inside the treated grain mass Rojht et al, 2010;Shams et al, 2011). In addition, it presents advantages such as low toxicity for mammals and to the environment, leaves no harmful residues in the treated product, is effective against species of insects resistant to insecticides, is persistent and stable at high and low temperatures, and does not affect the quality of the product (Subramanyam & Roesli, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation